THE BEGUILING ALLURE OF RUINS - Pellapaisiotis, Haris (Design/Arts/Culture, 2020)
This essay argues that the symbolic depiction of ruins through countless photographs and other forms of representation of the Nicosia Buffer Zone, rather than challenge the military division of the city, seems to sustain a territorial border mentality based on expectations of division and what a military zone should look like. It argues that the ruin is not simply a remnant of the past and therefore a signifier of what once was but is a physical space that can be occupied in the present as a catalytic site for experimentation in living and individuation.